Pengaruh Online Costumer Review terhadap Decision Purchase pada Konsumen Shopee dan Tokopedia - Karim, Fajri Alamsyah; Nurhasanah, Nunung; Nadeak, Banuara; Hartelina, Hartelina (Universitas Batanghari Jambi, 2024)
Online review factors have a crucial role in influencing consumer purchasing decisions on e-commerce platforms such as Shopee and Tokopedia. Online Customer Reviews are reviews that have been recorded by the e-commerce feature as opinions or comments felt by e-commerce buyers. These factors can influence Purchase Decisions. Positive online reviews can have an impact on other buyers as references who can then decide to purchase the desired product. This research method uses quantitative research involving a sample of 96 respondents using questionnaires. Then, the data obtained will be analyzed using simple linear regression analysis techniques. The results show that Online Customer Review is able to influence Purchase Decisions by getting a determination of influence contribution of 36.5%.